Analysis of Diversity in Advertising of Nonsurgical Cosmetic Procedures. Issue 9 (September 2021) - Yanes, Daniel A.; Kagha, Karen C.; Avram, Mathew M.
Abstract : Supplemental Digital Content is Available in the Text.